2022
DOI: 10.3390/foods11223565
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Apple Pomace Powder on the Bioactivity, and the Sensory and Textural Characteristics of Yogurt

Abstract: This study focused on the development of a yogurt with an improved structure, texture and antioxidant activity level, by using apple pomace (AP) powder that was obtained in large quantities during the production of juices. The objective was to determine the sensory, physicochemical, textural and antioxidant characteristics of yogurt with the addition of AP powder (0.2–1.0%), during its shelf life. The physicochemical composition of AP was determined as follows: dietary fibers—62.73%, including pectin—23.12%; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…However, the samples with apple pomace (C + AP and C + AP + LL16) were significantly yellower compared to C and C + LL16 in this study. The same pattern of b* coordinate was found in a study by Popescu et al [ 76 ], in which the yellow color was more intense when a higher apple pomace concentration was added to yogurt samples.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…However, the samples with apple pomace (C + AP and C + AP + LL16) were significantly yellower compared to C and C + LL16 in this study. The same pattern of b* coordinate was found in a study by Popescu et al [ 76 ], in which the yellow color was more intense when a higher apple pomace concentration was added to yogurt samples.…”
Section: Resultssupporting
confidence: 85%
“…Thus, apple pomace lowered the lightness of the supplemented cheeses samples. A 2022 study found that, as the apple pomace concentration increased (from 0.2% to 1.0%), the lightness (L*) values decreased from 77.27 to 73.36 in yogurt samples [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measure of influence of the storage period and concentrations of MBE added to the cream cheese samples on the texture parameters, the pH values and the sensory analysis (overall acceptability) were evaluated by analysis of mutual information. This mathematical modeling method was also applied in the study of the influence of storage days and the concentration of apple powder on the textural parameters and the general acceptability of yogurt, for 20 days [54]. The study of the influence of physicochemical quality indicators on the textural characteristics of dry-aged beef, for 35 days and different quantities of sea buckthorn and rose hip on the quality of flour products was also evaluated by applying analysis of mutual information [55][56][57].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Among these, phenols have been widely studied in recent years and are well known for their beneficial effects on human health and their ability to limit oxidative damage due to radical species [ 9 ]. Gorjanović et al (2020) studied AP flour obtained by dehydration (5 h, T ≤ 55 °C) and grinding (<300 μm) to apply as dietary supplement, while Popescu et al (2022) used AP powder, dried at 60 °C and crushed to 70 µm, to add during yogurt production [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%